American Orientalists on Collection and Compilation of the Qur’an: An analysis of Robert Spencer’s Views - Dr.Tariq Aziz; Rahim Ullah; Dr Tahira Batool; Prof. Dr.Muhammad Shahbaz Manj; Dr. Khair Muhammad Asif; Qammar aziz (Al-Qanṭara, 2023)
Orientalists have criticized Holy Quran for the satisfaction of their sinister and multifarious motives since dawn .There has been a great difference of opinion between Muslim scholars and the Orientalists on the preservation of book of Allah. They have refuted the services of companions in collection and compilation of the Quran. Robert Spencer is included in the list of those Orientalists who have completed their Quran commentaries and presented their views about this particular topic. This paper studies approach of Robert Spencer towards the preservation and compilation of the Qur’an. Like other western scholars and Orientalists, he claims that the existing Qur’an is not identical with the one that was offered by the Prophet Muhammad (PBUH) to his followers. He views that it was compiled by Muhammad’s companions after his death and in the process of compilation, Qur’an lost its originality. After the analytical study this paper reveals that the aforesaid stance is based on prejudice or willful ignorance about the textual history of the Qur’an. In fact, Qur’an was revealed by Allah Almighty and is completely preserved without even a minor change or disruption.